Learning Chinese as a second language in China: Positive emotions and enjoyment. (February 2021) - Zhang, Lubei; Tsung, Linda
Abstract: Exploring language learners' emotions and their role in facilitating language learning in different contexts has become the focus of much research in recent years. This present mixed-method study investigated the language learning enjoyment of Chinese as a Second Language (CSL) learners studying in Chinese universities. A corpus of 216 international students, mostly from Africa and Asia, participated in a questionnaire survey and 20 of them were invited to take part in follow-up interviews. Analysis of the survey data revealed a distinct three-factor structure underlying CSL learners' language learning enjoyment: Personal Fulfillment, Interpersonal Relations and Social Bonds. Personal Fulfillment was found to exert a significant direct effect on CSL learners' language learning enjoyment while the other two factors played an indirect role. This was well supported by the qualitative data from the follow-up interviews. The findings suggest that the structure of learners' language learning enjoyment may vary in different contexts but for CSL learners in China, especially for these adult CSL learners, a sense of fulfillment is the most effective booster for their learning enjoyment. Implications of the findings provide a better understanding of teaching CSL learners in China.